Temporal Trends of Infective Endocarditis in North America From 2000 to 2017—A Systematic Review. (25th September 2021) - Talha, Khawaja M; Dayer, Mark J; Thornhill, Martin H; Tariq, Wajeeha; Arshad, Verda; Tleyjeh, Imad M; Bailey, Kent R; Palraj, Raj; Anavekar, Nandan S; Rizwan Sohail, M; DeSimone, Daniel C; Baddour, Larry M
Abstract: Background: The objective of this paper was to examine temporal changes of infective endocarditis (IE) incidence and epidemiology in North America. Methods: A systematic review was conducted at Mayo Clinic, Rochester. Ovid EBM Reviews, Ovid Embase, Ovid Medline, Scopus, and Web of Science were searched for studies published between January 1, 2000, and May 31, 2020. Four referees independently reviewed all studies, and those that reported a population-based incidence of IE in patients aged 18 years and older in North America were included. Results: Of 8588 articles screened, 14 were included. Overall, IE incidence remained largely unchanged throughout the study period, except for 2 studies that demonstrated a rise in incidence after 2014. Five studies reported temporal trends of injection drug use (IDU) prevalence among IE patients with a notable increase in prevalence observed. Staphylococcus aureus was the most common pathogen in 7 of 9 studies that included microbiologic findings. In-patient mortality ranged from 3.7% to 14.4%, while the percentage of patients who underwent surgery ranged from 6.4% to 16.0%. Conclusions: The overall incidence of IE has remained stable among the 14 population-based investigations in North America identified in our systematic review. Standardization of study design for future population-based investigations has been highlighted for use in subsequent systematic reviews of IE.